Analisis Mean Length of Utterance (MLU) pada Anak Usia 3:11: Studi Kasus Gee di Kota Sorong, Papua Barat Daya - Frenny Silvia Pormes; Agustinus Lia Masan; Maria Sofiana Ritan Bunga (SOSCIED, 2026)
This study aims to describe the syntactic development of Gee, a 3-year-11-month-old girl living in Sorong City, Southwest Papua, Indonesia, using Mean Length of Utterance (MLU) analysis. The study was conducted due to the limited research on child language acquisition in the linguistic context of Southwest Papua, particularly studies employing MLU as an indicator of syntactic development. A descriptive qualitative approach supported by simple quantitative analysis was applied in this research. Data were collected through observation, recording of spontaneous speech, and transcription of Gee’s utterances during daily interactions with family members. The data were analyzed by calculating the total number of morphemes and utterances, determining the MLU value, and comparing the result with Brown’s stages of language development. The findings show that 464 morphemes were identified in 122 utterances, resulting in an MLU score of 3.80. Based on Brown’s classification, this score places Gee in Stage V of syntactic development. The findings further indicate that Gee was able to produce various sentence types, including declarative, interrogative, imperative, and negative sentences. In addition, the data reveal the influence of a bilingual environment through the use of Indonesian and Papuan Malay elements, as well as the influence of audiovisual media on vocabulary and pronoun choice. These findings suggest that Gee’s syntactic development is consistent with the typical language development characteristics of children of her age and is shaped by diverse linguistic inputs from her environment.